Differences in diagnostic power of STIR and T1W sequence in MR findings of bone bruise of acutely traumatized knee - Jelić, Đorđe R; Mašulović, Dragan; Milankov, Miroslav; Ristić, Branko; Jakovljević, Vladimir; Vojinović, Radiša (Medicinski časopis, 2024)
Introduction: Increasing use of magnetic resonance imaging (MRI) in acute knee trauma has led to increased awareness of bone bruises (BB). Posttraumatic BB is the only predictor of early osteoarthritis. The aim of our research is to determine the way in which it is possible to observe and precisely determine the localization, size, and number of BB, by the correct selection of MR imaging sequences. Material and methods: MR examinations of the knees performed during 2012-2013 in 100 subjects with an acute knee injury sustained during sports were retrospectively analyzed from the personal archive. All examinations were done in the first month after the trauma. Examinations were performed on an open-type MRI with a power of 0.3T. A standard protocol was used with sequences of spin echo T1-weighted in the sagittal plane, fat suppression T2-weighted in the sagittal, coronal, and axial planes, and Short Tau Inversion Recovery (STIR) in the coronal plane. The presence and arrangement of BB were analyzed. The difference in the frequency of BB findings in STIR compared to the T1W sequence and the assessment of the visibility of BB in both sequences were analyzed. Results: BB findings were observed in 51% of respondents. BB is the second, after effusion, the most frequent pathological finding on MR examination in acute knee trauma. A significant statistical difference was determined by the Wilcoxon test (Z=-5.067, p=0.000) between the T1W and STIR sequence, which indicates that the STIR sequence is convincingly more sensitive than the T1W sequence for the diagnosis of BB. Conclusion: It was concluded that better visibility of BB is given by STIR sequence compared to T1W sequence.
Keywords: Keywords: knee; sports; magnetic resonance; bone bruise; STIR; T1W.